The role of networking competencies in social enterprise performance - Sannikova, Aija; Titko, Jelena; Kudins, Janis (Business, Management and Economics Engineering, 2025)
Purpose – The goal of this research was to identify the need for networking competencies in social enterprises rated by the managerial personnel of social enterprises and academic staff of universities in Latvia.Research methodology – A survey among representatives of Latvian social enterprises and academic staff of Latvian higher education institutions (HEIs) was conducted. The data was processed by means of average ranking, Kruskal-Wallis H test, and one-way-ANOVA test.Findings – The analysis of the results of Latvian survey revealed that: 1) social enterprise per- sonnel and university academic staff rated the role of networking competencies in social enterprise performance differently; 2) social enterprises rated cooperation with local governments higher and with industry associations as less important than the group of university academic staff.Research limitations – The research is limited to the analysis of only networking competencies.Practical implications – The research results contribute to the institutional framework for the social entrepreneurship ecosystem through recommendations to universities in creating training programmes of social entrepreneurship competencies.Originality/Value – The conducted empirical study is the first study of its kind in the Latvian social enterprise ecosystem, and it offers unique data that can be used for planning the development of networking competencies.